Exploring key compounds in callicarpa longifolia: a study on isolation and identification - Md. Shakeel Alam; Shrivastava, Nidhi (Creative Pharma Assent, 2025)
Background: The present study aims to extract the bioactive phyto-components from the hydroalcoholic extract of Callicarpa longifolia. The study also aims to isolate and characterize the phytochemicals through quantitative and qualitative measures. Methodology: The mixture of Toluene, Ethyl Acetate, and Acetic Acid (8:4:0.4) was used as a solvent system with the thin-layer chromatography (TLC) technique. Twelve distinct spots were observed, indicating the presence of a variety of compounds with Rf values ranging from 0.12 to 0.89. The specific fractions were isolated using silica gel column chromatography, which was further analyzed with TLC. Results and Discussion: Fraction F showed consistency with standard terpenoids and was subjected to advanced analytical techniques for further evaluation. UV-visible spectroscopy identified a key absorption peak at 288 nm, while Fourier-transform infrared (FTIR) spectroscopy revealed functional groups such as alcohols, hydroxyls, alkanes, alkenes, and carboxylic acids. The compound's structure and proton environment were confirmed through ^1H Nuclear Magnetic Resonance (NMR) spectroscopy. The compound was identified as Methyl 3,11-dioxo-olean-12-en-28-oate with the molecular formula C₃₁H₄₆O₄, supported by mass spectrometry (M+ peak at 482.33 m/z). Conclusion: The significant bioactive terpenoids identified in the C. longifolia hydroalcoholic extract highlight its potential for developing therapeutic agents, particularly for anti-inflammatory and anticancer applications. The detailed phytochemical characterization provides a robust foundation for future studies exploring the pharmacological and clinical applications of C. longifolia. Quantitative analysis and advanced spectroscopic techniques confirmed the compound's identity and established its importance in medicinal chemistry.